Classification Analysis of Multiple Sclerosis Using Logistic Regression and SVM Algorithms - Laela, Ida Nur; Baihaqi, Wiga Maulana (Universitas Nusantara PGRI Kediri, 2024)
Health is the most important aspect to support daily activities. Of course, by having a healthy body, everyone can carry out various activities comfortably and calmly. Every individual certainly has a strong instinct to live a healthy life and be free from disease, one of which is by increasing the body's immunity. Multiple sclerosis (multiple sclerosis/MS) is a neurodegenerative autoimmune disease that affects the central nervous system. The affliction of MS is characterized by chronic inflammation, demyelination, gliosis, and neuronal death. The symptoms faced by MS patients are unpredictable, so there is a need for a classification related to the disease. Therefore, a classification study was carried out using the logistic regression algorithm and SVM. The method used in this research is a literature study with the Python programming language. The results of this study indicate that the SVM algorithm has a high accuracy rate of 88.33% of the logistic regression algorithm. So it can be concluded from this study that the SVM method has good performance for processing multiple sclerosis datasets.